dada a função real definida por f(x) = x²+x, calcule: f(1)+3f(-1)-2f(1/3)
Soluções para a tarefa
Respondido por
1
f(x)=x²+x
vamos calcular separados
f(1)=1²+1=1+1=2
f(-1)=(-1)²+(-1)=1-1=0
![f( \frac{1}{3} )=( \frac{1}{3} )^2+ \frac{1}{3} = \frac{1}{9}+ \frac{1}{3} = \frac{1+3}{9} = \frac{4}{9} f( \frac{1}{3} )=( \frac{1}{3} )^2+ \frac{1}{3} = \frac{1}{9}+ \frac{1}{3} = \frac{1+3}{9} = \frac{4}{9}](https://tex.z-dn.net/?f=f%28+%5Cfrac%7B1%7D%7B3%7D+%29%3D%28+%5Cfrac%7B1%7D%7B3%7D+%29%5E2%2B+%5Cfrac%7B1%7D%7B3%7D+%3D+%5Cfrac%7B1%7D%7B9%7D%2B+%5Cfrac%7B1%7D%7B3%7D++%3D+%5Cfrac%7B1%2B3%7D%7B9%7D+%3D+%5Cfrac%7B4%7D%7B9%7D+)
agora vamos calcular
![f(1)+3f(-1)-2f( \frac{1}{3} )= \\ \\ 2+3(0)-2( \frac{4}{9}) = \\ \\ 2+0- \frac{8}{9} = \\ \\ 2- \frac{8}{9} = \frac{18-8}{9} = \fbox{$ \frac{10}{9} $} f(1)+3f(-1)-2f( \frac{1}{3} )= \\ \\ 2+3(0)-2( \frac{4}{9}) = \\ \\ 2+0- \frac{8}{9} = \\ \\ 2- \frac{8}{9} = \frac{18-8}{9} = \fbox{$ \frac{10}{9} $}](https://tex.z-dn.net/?f=f%281%29%2B3f%28-1%29-2f%28+%5Cfrac%7B1%7D%7B3%7D+%29%3D+%5C%5C++%5C%5C+2%2B3%280%29-2%28+%5Cfrac%7B4%7D%7B9%7D%29+%3D+%5C%5C++%5C%5C+2%2B0-+%5Cfrac%7B8%7D%7B9%7D+%3D+%5C%5C++%5C%5C+2-+%5Cfrac%7B8%7D%7B9%7D+%3D+%5Cfrac%7B18-8%7D%7B9%7D+%3D+%5Cfbox%7B%24+%5Cfrac%7B10%7D%7B9%7D+%24%7D)
vamos calcular separados
f(1)=1²+1=1+1=2
f(-1)=(-1)²+(-1)=1-1=0
agora vamos calcular
Usuário anônimo:
OK!
Perguntas interessantes
Artes,
1 ano atrás
Geografia,
1 ano atrás
Artes,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Física,
1 ano atrás
Física,
1 ano atrás